(untitled) - Roger Peters (Monterey, California, 1980)
This book presents a comparative analysis of mammalian communication. First, each mammal's communication form a system. Only when communicative behaviors are presented together can the complex interactions an overlappings among them be explicated. Second, communication is part of the social and ecological systems peculiar to each mammal. Explanation of the adaptive significance of a particular form of communication often requires reference to these systems. Such references would be repetitous were they introduced anew for each message category for each mammal.
Keywords: animal communication,mammals - behavior